2007
DOI: 10.1007/s11423-007-9077-y
|View full text |Cite
|
Sign up to set email alerts
|

Interactive learning through web-mediated peer review of student science reports

Abstract: Two studies analyzed impacts of writing and receiving web-mediated peer reviews on revision of research reports by undergraduate science students. After conducting toxicology experiments, 77 students posted draft reports and exchanged doubleblind reviews. The first study randomly assigned students to four groups representing full, partial, or no peer review. Students engaging in any aspect of peer review made more revisions than students confined to reviewing their own reports. In the second study, all student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…Peleaz (2002) concluded that problembased writing with peer review led to improvements in learning for undergraduate students taking a physiology course "even when used to replace rather than supplement didactic lectures" (p. 181). Students are more apt to revise writing when peers review their writing when compared to self-review, -tions of factual mistakes, according to Trautmann (2009). Grammatical and spelling errors were not included in calculating the results.…”
Section: Peer Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peleaz (2002) concluded that problembased writing with peer review led to improvements in learning for undergraduate students taking a physiology course "even when used to replace rather than supplement didactic lectures" (p. 181). Students are more apt to revise writing when peers review their writing when compared to self-review, -tions of factual mistakes, according to Trautmann (2009). Grammatical and spelling errors were not included in calculating the results.…”
Section: Peer Reviewsmentioning
confidence: 99%
“…86% strongly agreed or agreed with a statement asking if review-GRAND CANYON UNIVERSIT Y ing other students' work helped improve their own writing. Trautmann's (2009) study also involved a qualitative component. Many students expressed positive comments regarding the peer review experience.…”
Section: Peer Reviewsmentioning
confidence: 99%
“…(4,7,9) (3,5,8) (7,9,10) (9,10,10) (3,5,6) A 2 (4,7,9) (9,10,10) (7,9,10) (9,10,10) (7,9,10) A 3 (3,5,8) (9,10,10) (9,10,10) (4,7,9) (4,7,9) Table 3: Peer assessments of all 5 criteria.…”
Section: ) Correctness Of the Factual Contents (Issue 1) (C 1 ) 2) Cmentioning
confidence: 99%
“…Recommendations of involving students in assessment and feedback can be frequently found in the higher education literature [2][3][4]. The online environment and various eLearning platforms allow for a high level of automation of tasks with regards to assessment, such as easy collection of answers, anonymization of results, and the possibility to create tools for collecting assessments [5]. Using assignments, exercises, and essays are a natural part of eLearning as the face-to-face interaction is often limited.…”
Section: Introductionmentioning
confidence: 99%
“…It adds a valuable dimension to learning. Trautmann 15 argues that "despite the primarily goals related to improving students communication and critical-thinking skills, deepening conceptual understanding, increasing motivation and responsibility for their own learning, using peer review as an educational tool can help understanding how the scientific community interacts to construct, revise and disseminate knowledge claims" (Tables 1, 2).…”
Section: Evidence Of Pedagogical Benefits Of Peer Reviewmentioning
confidence: 99%